The chronic kidney disease epidemiology collaboration equation combining creatinine and cystatin C accurately assesses renal function in patients with cirrhosis. Issue 1 (December 2015) - Krones, Elisabeth; Fickert, Peter; Zitta, Sabine; Neunherz, Stefan; Artinger, Katharina; Reibnegger, Gilbert; Durchschein, Franziska; Wagner, Doris; Stojakovic, Tatjana; Stadlbauer, Vanessa; Fauler, Günter; Stauber, Rudolf; et al.
Abstract Background Accurate measurement of renal function in cirrhotic patients is still challenging. To find the best test for the determination of the true glomerular filtration rate (GFR) in cirrhotic patients this study prospectively compared measured (m)GFR, the gold standard, with estimated (e)GFR using equations based on serum levels of creatinine and cystatin C. Methods GFR was measured by sinistrin clearance using the bolus method in 50 patients with cirrhosis (Child Turcotte Pugh score A, B and C) and 24 age-matched healthy subjects as controls. Measured (m)GFR was compared to eGFR using bias, accuracy 10 % and 30 %, as well as correlation coefficients. Results Creatinine-based equations generally overestimated GFR in patients with cirrhosis and showed a bias (average difference between mGFR and eGFR) of −40 (CG), −12 (MDRD) and −9 (CKD-EPI-Cr) ml/min/1.73 m2 . Cystatin C-based equations underestimated GFR, especially in patients with Child Turcotte Pugh score C (bias 17 ml/min/1.73 m2 for CKD-EPI-CysC). Of these equations, the CKD-EPI equation that combines creatinine and cystatin C (CKD-EPI-Cr-CysC) showed a bias of 0.12 ml/min/1.73 m2 as compared to measured GFR. Conclusions The CKD-EPI equation that combines serum creatinine and cystatin C measurements shows the best performance for accurate estimation of GFR in cirrhosis, especially at advanced stages.